Analysis Of Anxiety Level And Exercise In Pregnancy With Sleep Quality In Pregnant Women In The III Trimester - Herlinda, Herlinda; Widyaningsih, Sari; Elvina, Ade; Tariza, Tariza (Program Studi Kebidanan Fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Masalah: Kebutuhan istirahat tidur apabila belum terpenuhi akan berpengaruh terhadap kesehatan janin. Ibu hamil memerlukan sekitar delapan jam untuk tidur dimalam hari, selain itu tidur siang juga dibutuhkan oleh ibu hamil ketika memasuki trimester II dan III semakin banyak keluhan-keluhan yang dirasakan ibu sehingga menggangu istirahat pada waktu tidur. Tujuan: Penelitian ini dilakukan agar diketahuinya hubungan tingkat kecemasan dan senam hamil dengan kualitas tidur ibu hamil trimester III di Wilayah Kerja Puskesmas Pajar Bulan Kabupaten Seluma. Metode: Jenis penelitian adalah analitik menggunakan cross sectional design, dengan total sampling sebanyak 50 ibu hamil TM III. Menggunakan data primer, diolah secara univariat dan bivariat dengan analisis uji chi square. Hasil: Hasil penelitian diketahui 56,9% ibu hamil TM III dengan kualitas tidur baik, 68,0% ibu hamil TM III mengalami cemas, 70,0% ibu hamil TM III tidak senam hamil, ada hubungan tingkat kecemasan dengan kualitas tidur ibu hamil trimester III (p value = 0,006) dan ada hubungan senam hamil dengan kualitas tidur ibu hamil trimester III (p value = 0,002). Kesimpulan: Ada hubungan tingkat kecemasan dengan kualitas tidur ibu hamil trimester III di Wilayah Kerja Puskesmas Pajar Bulan Kabupaten Seluma, dengan p value = 0,006 dan Ada hubungan senam hamil dengan kualitas tidur ibu hamil trimester III di Wilayah Kerja Puskesmas Pajar Bulan Kabupaten Seluma, dengan p value = 0,002. Saran: Hasil penelitian ini hendaknya menjadi acuan bagi petugas Puskesmas Pajar Bulan khususnya bagi program KIA agar meningkatkan edukasi kepada ibu hamil TM III terkait berbagai hal mengenai kehamilan dan persiapan persalinan dengan melibatkan suami atau orang terdekat. Kata Kunci : Kualitas Tidur, Tingkat Kecemasan, Senam Hamil. ABSTRACT Background: If the need for sleep rest is not met, it will affect the health of the fetus. Pregnant women need around eight hours of sleep at night. Apart from that, pregnant women also need naps when they enter the second and third trimesters. The more complaints the mother experiences, the more it interferes with her rest at bedtime. Objective: This research was conducted to determine the relationship between anxiety levels and pregnancy exercise with the sleep quality of pregnant women in the third trimester in the Pajar Bulan Community Health Center Working Area, Seluma Regency. Method: The type of research was analytical using a cross sectional design, with a total sampling of 50 TM III pregnant women. Using primary data, processed univariately and bivariately with chi square test analysis. Results: The results of the study showed that 56.9% of pregnant women in TM III had good sleep quality, 68.0% of pregnant women in TM III experienced anxiety, 70.0% of pregnant women in TM III did not exercise during pregnancy, there is a relationship between the level of anxiety and the quality of sleep of pregnant women in the third trimester. (p value = 0.006) and there is a relationship between pregnancy exercise and the sleep quality of pregnant women in the third trimester (p value = 0.002). Conclusion: There is a relationship between anxiety levels and the sleep quality of third trimester pregnant women in the Pajar Bulan Community Health Center Working Area, Seluma Regency, with p value = 0.006. There is a relationship between pregnancy exercise and the sleep quality of pregnant women in the third trimester in the Pajar Bulan Health Center Working Area, Seluma Regency, with p value = 0.002. Suggestion: The results of this research should be a reference for Pajar Bulan Community Health Center officers, especially for the KIA program, to increase education for TM III pregnant women regarding various matters regarding pregnancy and preparation for childbirth by involving their husbands or those closest to them. Keywords : Anxiety Level, Pregnancy Exercise, Sleep Quality,.